Police supervision: perspectives of subordinates. Issue 1 (20th March 2017) - Cronin, Shea; McDevitt, Jack; Cordner, Gary
Abstract : Purpose: Given the central role of supervision in shaping police agency outcomes and the impact of the supervisor-subordinate relationship, the purpose of this paper is to understand subordinates' ratings of supervisor performance overall and on several distinct dimensions. Design/methodology/approach: Descriptive and explanatory analyses are conducted on subordinate views of supervision based on a survey of officers and detectives ( n =7, 085) in 89-agencies. Findings: Reporting high ratings of supervisor performance overall, subordinates also view supervisors as fair, supportive and engaged in practices that set expectations. These dimensions are highly correlated with overall satisfaction; other variables, such as age, race and gender demonstrate weak relationships to overall satisfaction and perceptions of fairness, support and direction. Research limitations/implications: The study is based on subordinates' perceptions of supervisors and does not address the supervisors' own perceptions or actual behavior. Future studies should collect identical information from supervisors as well as examine agency-level variation in both subordinate and supervisor outlooks and styles. Practical implications: The results support modern approaches to police supervision that emphasize not just direction and control but also fair and supportive relationships with subordinates. Originality/value: The study examines the views of thousands of line-level police across a large number of representative US agencies and explores relationships using a comprehensive set of variables.